Financing Protection of the Global Commons : The Case for a Green Planet Contribution - Clemencon, Raymond (Global Environment Facility, 2017)
This paper argues that new, more automatic fundraising approaches promise to be more effective than the traditional approach in raising adequate and predictable resources to help developing countries respond to global environmental challenges. An annual green planet contribution of United States (U.S.) 2 dollars levied on some polluting activity and paid by applicable individual citizens of developed countries will raise about twice the amount of resources currently available from both multilateral and bilateral sources for global environmental measures in developing countries. The following analysis discusses why such a fund-raising approach for protecting global commons in developing countries will be superior to the existing mechanism and why it holds the promise of securing adequate and predictable resource flows in the coming decades. The present analysis builds on recent experience with new market-based approaches to domestic environmental policy-making in Organization for Economic Co-operation and Development (OECD) countries. The paper discusses various options for levying a global environmental charge or user fee with respect to such factors as ease of implementation, political acceptability, and fund-raising potential. It concludes that a personal green planet contribution levied annually with car registration renewal may be the most promising, albeit not the only, option worth considering.